Pengaruh Pelatihan Pasar Modal, Return Investasi, Persepsi Risiko, Dan Literasi Keuangan Terhadap Minat Investasi Melalui Aplikasi Online Pada Generasi Z. - Kamilatur Ro’fati; Sri Rahayuningsih (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
The purpose of this research is to find out whether there is an effect of Capital Market Training(X1), Investment Return(X2), Risk Perception(X3), and Financial Literacy(X4) on Generation Z Invesment Interst, either partially or simulaneously.. The method used in this study is a quantitative research method, using a questionnaire data collection tool, with a Generation Z at the University of 17 August 1945 Surabaya Faculty of Economics and Business Undergraduate 1 year 2019-2020 class as the population. The results of this study are that there is an effect of capital market training(X1) on the z generation's investment interest, there is an effect of investment return(X2) on the z generation's investment interest, no effect of risk perception(X3) is found on the z generation's investment interest, and there is an influence of literacy finance(X4) to investment interest in generation z. But if tested Simultaneously all Variables have a Significant effect.